Students’ perception of teacher in using bilingual in EFL classroom: Indonesian context - Syahruzah, Juang Kurniawan (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The objective of this research is the importance of use bilinguals to improve the students’ ability in English, the use of the both of languages is very important to help students to understand the English material delivered by the teacher. Besides that, it makes it easy for them to understand the meaning of vocabulary and English sentences and also make them feel comfortable in taking English lessons. To explore students’ knowledge about the effect of using bilingual the use of English and Indonesia to improve their ability in English learning, the researcher conducts a study of “Students’ Perception of the Importance of Using Bilingual in English Learning Ability. The result of this study was the students had positive perception toward the importance of using bilingual (Bahasa Indonesia and English) in English learning process. The data analysis of the information obtained from the questionnaire and the interview confirmed these results. The questionnaire data showed that from 10 statements, there are 9 statements had the “Strongly Agree” response of the students. It was proven by the central tendency of each statements got the average above “80%” which is based on assessment interval on Likert Scale where index 80%-100% means “Strongly Agree”.